Black Arsenic–Phosphorus: Layered Anisotropic Infrared Semiconductors with Highly Tunable Compositions and Properties. (25th June 2015) - Liu, Bilu; Köpf, Marianne; Abbas, Ahmad N.; Wang, Xiaomu; Guo, Qiushi; Jia, Yichen; Xia, Fengnian; Weihrich, Richard; Bachhuber, Frederik; Pielnhofer, Florian; Wang, Han; Dhall, Rohan; et al.
<x xml:space="preserve">Abstract</x> New layered anisotropic infrared semiconductors, black arsenic–phosphorus (b‐AsP), with highly tunable chemical compositions and electronic and optical properties are introduced. Transport and infrared absorption studies demonstrate the semiconducting nature of b‐AsP with tunable bandgaps, ranging from 0.3 to 0.15 eV. These bandgaps fall into the long‐wavelength infrared regime and cannot be readily reached by other layered materials.